Social Science Preserves Teachers's Competence of Self- sufficience Levels - Oguz, Sibel (Elsevier BV, 2015)
AbstractThe determination of the self-efficacy levels of pre-service social sciences teachers in terms of constructivist education may enable individuals to know themselves better. This may help pre-service social sciences teachers be prepared for education world, too. Thus, the present study investigated whether the self-efficacy levels of students attending the social sciences education department of faculty of education at Kastamonu University in terms of constructivist education varied by the demographic variables related to students. The study aimed at examining the self-efficacy levels of social sciences education department students based on various variables. To this end, survey model was employed in the study whose universe consisted of the social sciences education department students attending the faculty of education at Kastamonu University in the spring semester of the 2010-2011 academic year. The research sample was composed of 279 first grade, second grade, third grade, and fourth grade social sciences education department students attending the faculty of education at Kastamonu University, who participated in the study on a voluntary basis. The “Scale for Determining the Self-Efficacy Beliefs of Pre-Service Social Sciences Teachers In Terms Of Constructivist Education”, developed by Çınar (2010), was used in the study. The Cronbach's Alpha value of the scale was found to be 0.96.
Keywords: preservice teachers; self-sufficience; social sciences; 2. Zero hunger; 4. Education